Pelatihan Instalasi Jaringan Komputer Menggunakan Simulasi Cisco pada SMK Methodist Tanjung Morawa - Frans Mikael Sinaga; Sio Jurnalis Pipin; Heru Kurniawan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
SMK Swasta Methodist Tanjung Morawa is one of the private schools under the auspices of Yayasan Methodist Kasih Imanuel Indonesia, which was established in 2008. Tanjung Morawa Methodist Private Vocational School has various majors, one of which is Network and Computer Engineering (TKJ). Network installation is one of the most interesting subjects to discuss because the students have studied it before and it is already a lesson that is in accordance with the majors of the students of Tanjung Morawa Methodist Private Vocational School, namely Computer Network Engineering (TKJ). The students have learned several computer network simulation applications such as virtual boxes but the network simulation applications studied are still limited, therefore, the Faculty of Informatics Universitas Mikroskil offers activities in the form of computer network installation training using Cisco simulation to improve the ability of students to have better competencies. This training activity lasted for 2 days and was carried out in the computer laboratory of Universitas Mikroskil. During this training activity the students were given pre-test questions, materials and case studies, post-test and final feedback.